Dual Based Assessment in Improving the Quality of Skills at the Center of Excellence Vocational School - Suwandi, Suwandi; Hanafiah, Hanafiah; Iriantara, Yosal; Sulastini, Rita (International Journal of Educational Research & Social Sciences, 2022)
This research is motivated by various problems related to the quality and relevance of Indonesian education which are the main issues. Indicators of quality education are marked by graduates who have superior competencies and are able to compete in the business world and industry for graduates from Vocational Secondary Education. Quality vocational education applying quality standards can contribute to the country's economic development, but it still cannot be realized optimally at the time of its implementation. Such conditions occur in SMK graduates in Indonesia so that the open unemployment of SMK graduates is getting bigger. It is interesting to do further research to find out why and how this happened and find solutions to the problems faced. Dual Based Assessment (DuBA) on the vocational skills aspect is expected to be a solution in ensuring the quality of skills at the Center of Excellence Vocational High School and Vocational Schools in general. In particular, this study describes and analyzes the "Daming Cycle" quality management approach from William Edward Deming, with its management principles approach which include: Plan, Do, Check and Action Dual Based Assessment in Improving Skills Quality at SMK Center of Excellence. The research method used is qualitative with a case study approach through interview data collection techniques, documentation studies and observations at the research location of Pertiwi Kuningan Vocational School, West Java. The results obtained in this study In particular, this study describes and analyzes the "Daming Cycle" quality management approach from William Edward Deming, with its management principles approach which include: Plan, Do, Check and Action Dual Based Assessment in Improving Skills Quality at SMK Center of Excellence. The research method used is qualitative with a case study approach through interview data collection techniques, documentation studies and observations at the research location of Pertiwi Kuningan Vocational School, West Java. The results obtained in this study In particular, this study describes and analyzes the "Daming Cycle" quality management approach from William Edward Deming, with its management principles approach which include: Plan, Do, Check and Action Dual Based Assessment in Improving Skills Quality at SMK Center of Excellence. The research method used is qualitative with a case study approach through interview data collection techniques, documentation studies and observations at the research location of Pertiwi Kuningan Vocational School, West Java. The results obtained in this study The research method used is qualitative with a case study approach through interview data collection techniques, documentation studies and observations at the research location of Pertiwi Kuningan Vocational School, West Java. The results obtained in this study The research method used is qualitative with a case study approach through interview data collection techniques, documentation studies and observations at the research location of Pertiwi Kuningan Vocational School, West Java. The results obtained in this study The quality of the results of the DuBA approach at Pertiwi Kuningan Vocational School has led the school to become one of the Center of Excellence Vocational Schools in West Java so that it deserves to be a reference vocational school that has the obligation to carry out an impacting program on the surrounding vocational schools. The quality of skills in Axioo's Industrial Class has contributed to the decline in the unemployment rate for vocational school graduates, on the other hand, these graduates have been able to participate in driving the economy on a micro scale by becoming employees in various business fields and opening up entrepreneurial opportunities.